Criminological Factors Against Cockfighting Gambling Crimes - Romanus Arindi Rapok; Karolus Kopong Medan; Heryanto Amalo (LUTUR Law Journal, 2026)
This study aims to analyze the criminogenic factors contributing to cockfighting gambling and the efforts to overcome it in Central Adonara District, East Flores Regency. Cockfighting gambling remains prevalent despite being prohibited under Indonesian criminal law. This phenomenon not only violates legal norms but also creates social problems, including increased criminal activity and public disorder. This research employs an empirical legal research method with a case approach. Data were collected through interviews, observations, and literature studies involving 13 respondents, including government officials, community leaders, religious figures, and gambling participants. The data were analyzed qualitatively. The results show that the criminogenic factors influencing cockfighting gambling include economic conditions, environmental influences, cultural traditions, weak social and religious control, and ineffective law enforcement. Additionally, the practice is sustained by community perceptions that view it as part of local tradition. Efforts to combat this issue include pre-emptive, preventive, and repressive measures; however, these efforts have not been fully effective due to weak coordination among stakeholders and limited supervision. In conclusion, cockfighting gambling in Central Adonara District is driven by complex factors and requires comprehensive handling through synergy between law enforcement agencies, local government, and the community.